Review of the manual “Transport Economy” - Paliulis, Habil N. (Transport, 2003)
The manual prepared by the lecturers of the Transport Management Department of Vilnius Gedirninas Technical University is intended for students ot transport. The manual will be useful to the students of Transport management and economy, as well as to the postgraduates studying the subjects of the following modules: TITVB 05010 - Transport economy, TITVM 03059 - Transport enterprise economy, TITVB 06025 - Road transport economy, TITVB 08027 - Air transport economy, TITVB 08027- Water transport economy, TITVB 07026 - Railway transport economy, TITVB 6007 - Economy of international transpo1i services, TITVB 5002 - Commercial operation of railway transport. The manual may also serve the needs of students of other transport specialities in preparing an individual course or final papers. First Published Online: 19 Dec 2011